Pendampingan UMKM melalui pengembangan identitas usaha dalam meningkatkan keterampilan menggunakan aplikasi Canva - Pramesti, Salwa Sensio Ayu; Ubaidillah, Moh. (Nur Science Institute, 2023)
Rapid technological developments in the digital era have created new habits, such as moving all types of activities online. In this digital era, people are more interested in choosing fast and easy methods. Therefore, MSME players must act more quickly and efficiently to keep pace with current developments. Based on this, MSME actors must be responsive to changes. However, in reality, there are still many MSME entrepreneurs who still need help utilizing existing technology. This condition makes it difficult for MSMEs to compete with competitors. One strategy that can be implemented is to emphasize business identity, such as a name, logo, symbol, or a combination of these, which aims to identify a product or service and differentiate it from competitors. Based on the problems above, community service activities were carried out using implementation methods in the form of training, mentoring, and implementing business identity strategies. From the results of community service, the program ran smoothly and effectively because MSMEs gained knowledge and skills they had never obtained before.